Students` Perception of Service Quality in Higher Educational Institutions in Ghana and Its Effects on their Loyalty - Zakari, B. (University of Ghana, 2016)
The proliferation of higher educational institutions has given students a wider variety of options as to where to persue their studies. In this era of competition, measuring service quality in higher education has become a vital tool to determine the level of students` perception of service quality in order to achieve their loyalty. This study focuses on Ghanaian students’ perception of service quality in higher educational institutions and its effects on their loyalty. The SERVQUAL model was adopted as a conceptual framework for this study. The study sought to examine the interaction and non-interaction effects of service quality dimensions, institutional reputation and level of education on students’ satisfaction and loyalty. The quantitative approach was adopted, using a questionnaire to collect data from 379 students attending the University of Ghana Business School. Regression analysis and the structural equations model (SEM) were used to analysed the data. The findings revealed, that there is a variation in the key service quality dimension that were peculiar to the undergraduate and post graduate students. Tangibles, assurance, institutional reputation and responsiveness were found to be peculiar to undergraduates; whereas, institutional reputation, tangibles and empathy were found to be crucial to postgraduate students. Finally, findings from the study revealed that institutional reputation plays a vital role in predicting students` satisfaction and loyalty. The study therefore, recommended that managers of higher educational institutions should concentrate on institutional reputation as a strategic tool in achieving students’satisfaction and loyalty. Again, it is recommended that managers of higher educational institutions identify the specific quality dimensions that are peculiar to students at different levels, and design a different service quality strategy for these groups, in their quest to achieve students` satisfaction and loyalty.
Theses (MPhil.) - University of Ghana, 2016